2020
DOI: 10.35311/jmpi.v6i01.52
|View full text |Cite
|
Sign up to set email alerts
|

Efek Antidiabetes Kombinasi Ekstrak Etanol Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Dan Daun Salam (Syzygium polyanthum Wight.) Pada Tikus Putih Dengan Metode Induksi Aloksan

Abstract: Diabetes melitus ditandai dengan terjadinya hiperglikemi. Indonesia merupakan negara menempati urutan ke 7 dengan penderita DM sejumlah 8,5 juta. Penggunan obat bahan alam sudah banyak digunakan secara empiris oleh masyarakat, diantaranya ekstrak daun pandan wangi dan daun salam masing-masing telah dilaporkan memilikiefek hipoglikemik dan berpotensi sebagai antioksidan yang dapat memperbaiki sel-sel tubuh yang rusak, termasuk pankreas. Tujuan penelitian ini adalah untuk mengetahui kombinasi Ekstrak Daun Pandan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The antioxidant activity allows flavonoids to capture or neutralize free radicals to repair damaged tissue. (Lolok, et al 2020;Dewanti, et al 2017). In this study, it was found that there was a reasonably good flavonoid content from the extraction method that had been carried out so that it was able to affect the healing of cuts in rats which can be seen in the results of the research parameters that have been described, this is also reinforced by research conducted by Dewi et al (2019) in pandan leaf plants which from the results of his research showed the optimum flavonoid content with a long extraction time of 40 minutes which was 7.1%, which means that an increase in temperature and extraction time will affect the compounds in solution, the extraction temperature is too high and the extraction time is too high.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity allows flavonoids to capture or neutralize free radicals to repair damaged tissue. (Lolok, et al 2020;Dewanti, et al 2017). In this study, it was found that there was a reasonably good flavonoid content from the extraction method that had been carried out so that it was able to affect the healing of cuts in rats which can be seen in the results of the research parameters that have been described, this is also reinforced by research conducted by Dewi et al (2019) in pandan leaf plants which from the results of his research showed the optimum flavonoid content with a long extraction time of 40 minutes which was 7.1%, which means that an increase in temperature and extraction time will affect the compounds in solution, the extraction temperature is too high and the extraction time is too high.…”
Section: Discussionmentioning
confidence: 99%
“…The criterion for effective induction was fasting glucose >125 mg/dL. 18 The nanoparticle granules of the sunkist orange peel extract were administered for 14 days. The rats were euthanized and necropsied to obtain cardiac and aortic organs, which were preserved in liquid formalin for 1 d. Subsequently, the heart organs were washed using physiological NaCl solution, weighed, and fixed in 10% Neutralized Buffered Formaldehyde (NBF) for histological staining.…”
Section: Methodsmentioning
confidence: 99%
“…World Health Organization (WHO) melaporkan bahwa 177 juta penduduk dunia yang menderita Diabetes Mellitus, dan sekitar 80% diantaranya berada di Negara berkembang. Penderita DM di Indonesia menempati urutan ke 7 berjumlah 8,5 juta setelah Cina, Amerika Serikat, Brazil, dan Rusia [10].…”
Section: Pendahuluanunclassified